Leaning against the wind policies on Vietnam's economy with DSGE model - Phuc Huynh; Trang Nguyen; Thanh Duong; Duc Pham (Economies, 2017)
The global financial crisis of 2007-2008 had a negative impact on many countries, including Vietnam. Many policies have been applied to stabilize the macro-economic indicators. However, most of them are based on old qualitative models, which do not help policy makers understand deeply how each one affects the economy. In this paper, we investigate a quantitative macro-economic approach and use leaning against the wind policies with the Dynamic Stochastic General Equilibrium model (DSGE) to find a better way to understand how policies stabilize the Vietnamese economy. Based on the framework of Gerali et al., we calibrate the hyper-parameter for Vietnam financial data and do the comparison between the standard Taylor rule and the cases in which we add asset price and credit elements. The results show that the credit-augmented Taylor rule is better than the asset-price-augmented one under the technology shock and contrary to the cost-push shock. Moreover, the extended simulation result shows that combining both asset-price and credit rules on the model is not useful for Vietnam's economy in both types of shock.
Keywords: C68; E00; E12; E52; E62; 330; Taylor rules; monetary policy; leaning against the wind; macro-economy; Vietnam financial market; DSGE; inflation